Buchwaldoboletus xylophilus and Phlebopus portentosus, two non-ectomycorrhizal boletes from tropical China - Xie, Hui-Jing; Zhang, Chun-Xia; He, Ming-Xia; Liang, Zhi-Qun; Deng, Xiao-Hua; Zeng, Nian-Kai (Phytotaxa, 2021)
Buchwaldoboletus xylophilus and Phlebopus portentosus (Boletales) are two non-ectomycorrhizal boletes, which are widely reported in tropical Asia. However, there is little information available about the taxonomy of these two boletes. Here, B. xylophilus and P. portentosus are redescribed based on morphology and molecular phylogenetic analyses of DNA sequences from nuclear 28S rDNA (28S), nuc rDNA internal transcribed spacer region ITS1-5.8S-ITS2 (ITS), translation elongation factor 1-α gene (TEF1) and the RNA polymerase II second largest subunit gene (RPB2). Detailed descriptions, color photos of fresh basidiomata, and line-drawings of microscopic features of the two taxa are presented.